Oral Findings, Salivary Copper, Magnesium, and Leptin in Type II Diabetic Patients in Relation to Oral Candida Species - Mohammed Jasim Mohammed; Abbas S. Al-mizraqchi; Salah M. Ibrahim (International Journal of Microbiology)
Background. Type 2 diabetes is a condition in which the body becomes resistant to the effects of insulin, leading to reduced insulin production in the pancreas. It has genetic- and family-related risk factors that cannot be changed, along with modifiable lifestyle factors. The precise genetic causes of type 2 diabetes are still unknown. However, individuals can potentially slow or stop the progression of the condition by making dietary adjustments and increasing physical activity levels. Material and Methods. Forty-five type II diabetic patients in the study included participants between 40 and 60 years old, with a minimum duration of one year, as well as 45 healthy control subjects who were matched in terms of age and sex, and had no underlying systemic diseases. Oral examination is done for the symptoms including burning sensation, candidiasis, and a reduction in the production of saliva. The rate of saliva flow (in milliliters per minute) was measured in samples of saliva that were not stimulated. The salivary trace elements and levels of adipocytokines were evaluated using colorimetric and Ethylenediaminetetraacetic acid (ELISA) testing. The quantification of Candida colony numbers, an enrichment and culture approach, was used to achieve a concentration of 100,000 colony-forming units per milliliter (CFU/ml). The ShowNovo WG1 halimeter was used to measure volatile sulfur compounds in breath. The salivary glucose oxidase assay was conducted using a colorimetric technique, while the determination of trace elements was also performed using a colorimetric assay method. Result. The diabetic group exhibited a significant increase in the number of Candida spp colonies due to elevated levels of glucose in the saliva (p>0.05). However, the variables being examined, such as body mass index (BMI), burning mouth syndrome (BMS), salivary flow rate (SFR), salivary leptin, salivary copper, and salivary magnesium, did not exhibit any significant variations in quantities between the diabetic and healthy groups (p>0.05). Conclusion. The data collected in this research aid in the creation of a preventative program for oral fungal infections in individuals with type 2 diabetes. The program utilizes saliva and its constituents.